L’intervention cognitive-développementale auprès des adolescents délinquants - Dionne, Jacques (Criminologie, 1996)
In the last decades, many types of intervention, seeking to alter the subject's level of cognition, have been developed for the rehabilitation of young delinquents. Among these different cognitive models, some are inspired by developmental-cognitive psychology, which has been used to improve rehabilitation and prevention initiatives.This article's objective is to make the developmental-cognitive approach known, in order to make intervention models more accurate and to help these youngsters improve their ability in building and maintaining interpersonal relationships, as well as their sense of responsibility and their moral judgment.The first part of the article introduces the general characteristics , of developmental-cognitive psychology. The second describes intervention methods which were developed from these theoretical principals. And the third section presents the developmental-cognitive intervention model as it is currently applied in the experimental differential intervention project with teenagers in difficulty, who were placed in rehabilitation internship in Montreal.